Self-stratifying powder coatings based on eco-friendly, solvent-free epoxy/silicone technology for simultaneous corrosion and weather protection - Kargarfard, Neda; Simon, Frank; Schlenstedt, Kornelia; Ulischberger, Lisa; Voit, Brigitte; Gedan-Smolka, Michaela; Zimmerer, Cordelia (Progress in Organic Coatings, 2021)
A melt-based self-stratifying coating based on silicone/epoxy blend systems is reported as an easy-to-use, eco-friendly, and industrial favorable procedure. The powder forms of the silicone and epoxy resins were mixed either by dry-blending or co-melt-mixing processing method, and blends were electrostatically applied onto steel sheets and cured. Self-stratification of cured coatings with a thickness of 100 ± 30 μm occurred and was investigated by an adopted ATR-FTIR method and consolidated SEM-EDX and X-ray photoelectron spectroscopy. Fundamental studies on influencing parameters on phase separation and stratification in coatings such as surface tension, the mass ratio of silicone/epoxy resins, crosslinking reaction, and manufacturing processes were performed and discussed in detail. It is corroborated that the dry-blending of methyl substituent silicone resin with the high and medium molecular weight epoxy resins at a 1/3 mass ratio (silicone/epoxy) leads to a complete stratification structure (Type I), having the silicone phase located on the top of the coating and the epoxy phase towards the steel surface, resulting in good adhesion. 3/1 mass ratio of the silicone/epoxy blends led to the dispersion of epoxy droplets into the silicone matrix (Type IV) and 1/1 mass ratio, showed lateral phase separation morphology. The co-melt-mixing process was yielded the formation of a thin homogenous layer of silicone phase on the top surface of the coating and a mixture of large and small drops of silicone dispersed into the epoxy matrix (Type I–Type III). Finally, the protective properties of the silicone/epoxy self-stratifying coatings with different stratification structures were evaluated.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Corrosion and weather protection; Epoxy resin; IR spectroscopy; Phase separation; Self-stratifying powder coatings; Silicone resin